Advancing the use of the repertory grid technique in the built environment: A systematic review - Rahman, Rawan; Bidoun, Dana; Agiel, Ahmed; Albdour, Ala' (Frontiers in Built Environment, 2022)
Since the development of personal construct theory, the repertory grid technique (RGT) has been the most recognized tool to elicit personal constructs. Although RGT was found to be a viable scientific and practical method in different fields, its utilization in the built environment has been extremely limited. Therefore, this study aimed to explore RGT as a research method and advance its use in the built environment field. Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, this study conducted a systematic review to identify studies on Scopus that have used RGT before 2021. These studies were investigated according to subject area, location, year of publication, aim, and research design. Among the 782 studies contributing to more than 24 subject areas, 30 used RGT within the built environment scope. Results indicated the validity of RGT to the built environment by exploring different ways it may be employed. This review strongly recommends advancing the use of RGT in the built environment and taking advantage of its potential.